Environmental Change in the Late Weichselian on the Kullen Peninsula - Dyson,Sarah (Dissertations in Geology at Lund University, 2025)
Kullatorpssjön is a small lake located on the Kullen peninsula. This was among the earliest land masses in Sweden to become ice-free, roughly 17,000 cal. BP, following the last deglaciation, and so forms a vital record of the pioneer floral and faunal history of Sweden. This thesis is part of a collaboration between palaeoecologists and archaeologists at Lund University and geoscientists at Stockholm University who are primarily looking to uncover when the first humans colonised Sweden, as well as to investigate pioneer vegetation and animal communities. A 4 m long sediment core was collected from Kullatorpssjön, which is undergoing palaeogenetic (sedaDNA) analysis in Stockholm. A chronology was constructed from this core sequence (KTS-2) against which sedaDNA analysis can be compared. The sequence covers the Late Glacial from 19-18,000 cal. BP to 11-10,000 cal. BP. Lithological and geochemical analyses were performed on the KTS-2 sequence, as well as an additional core sequence (KTS-4), on which X-ray fluorescence (XRF) core scanning was performed. XRF data reflect changes in detrital minerogenic input and aquatic productivity. In the uppermost segment of the KTS-4 sequence, K/Rb is used as a weathering indicator. The ratios Fe/Ti and Fe/S were used in the lower segment to identify greigite (iron sulphide) layers. Total organic carbon (TOC) content and carbon/nitrogen (C/N) data provide insight into productivity changes and origin of sediment and organic matter. These data were poorly represented in the KTS-2 sequence, so KTS-4 was analysed more deeply. Both KTS-2 and KTS-4 were correlated to a sequence retrieved in the 1990s, which established environmental change (Sandgren et al., 1999; Hammarlund, 1999). These previous studies include records of mineral magnetic data, ostracod and diatom assemblage data and stable oxygen- and carbon-isotope data. Once correlated together, these three sequences from Kullatorpssjön enabled the expansion and refinement of the current understanding of environmental change at Kullaberg over the Late Weichselian, providing context and dates for the first colonisation of Sweden following the last deglaciation.